Institutional Constraints To 4C Certification Impact On Smallholder Coffee Incomes In Indonesia - Muhammad Ibnu (The Indonesian Forestry Certification Cooperation, 2026)
This study critically examines the economic impact of the Common Code for the Coffee Community (4C) certification on smallholder coffee farmers in West Lampung and Tanggamus, Indonesia. Using a quasi-experimental design with Propensity Score Matching (PSM) applied to survey data from 400 farmers, the findings reveal that while certified farmers earn slightly more than their uncertified counterparts, the difference is not statistically significant. This outcome underscores a persistent gap between the intended benefits of sustainability standards and their realized impact on rural livelihoods. By integrating field-based qualitative insights, the study demonstrates that institutional weaknesses—such as externally driven farmer organizations, fragmented value chains, and limited collective bargaining capacity—undermine the transformative potential of certification schemes. These structural constraints explain why sustainability standards fail to generate meaningful improvements in smallholder incomes. The findings have direct implications for several Sustainable Development Goals (SDGs). First, they question the assumption that certification contributes automatically to SDG 1 (No Poverty) and SDG 8 (Decent Work and Economic Growth). Second, they highlight the reproduction of structural inequalities (SDG 10) within certified and non-certified market systems. Third, they challenge the efficacy of sustainability certification as a mechanism for responsible consumption and production (SDG 12), especially in the absence of institutional reforms. This study argues that certification must be embedded within empowered local institutions and equitable market arrangements to achieve inclusive development outcomes. Without addressing structural barriers, sustainability standards risk becoming technocratic instruments that offer symbolic compliance rather than substantive change.